2019
DOI: 10.3390/coatings9040278
|View full text |Cite
|
Sign up to set email alerts
|

A Zinc-Rich Coating Fabricated on a Magnesium Alloy by Oxide Reduction

Abstract: The corrosion resistance of magnesium alloys could be enhanced by covering metallic coatings on the surface. The zinc-rich coating is one of these metallic coatings. To fabricate a zinc-rich coating on magnesium alloys, the substrate should be pretreated carefully, and a protective atmosphere is usually required. In this research, a zinc-rich coating was successfully fabricated on the AZ91D magnesium alloy in air by a diffusion alloying method, with zinc oxide as the zinc source. At the same time, the pretreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In PVD, the coating material is first evaporated and subsequently condensed onto the substrate. The CVD process, on the other hand, is a chemical reaction that involves the deposition of solid material from a gas or vapour phase onto a heated metal surface [18]- [21]. The deposition of nanostructure coatings on the substrate is usually performed by gas phase deposition procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In PVD, the coating material is first evaporated and subsequently condensed onto the substrate. The CVD process, on the other hand, is a chemical reaction that involves the deposition of solid material from a gas or vapour phase onto a heated metal surface [18]- [21]. The deposition of nanostructure coatings on the substrate is usually performed by gas phase deposition procedures.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that Mg atoms would cross the MgO film and be oxidized into new MgO at the interface of the MgO film and the air. The surface alloying process could be simultaneous with oxidation of a magnesium alloy specimen. , Because Mg atoms could pass through the MgO film and be oxidized there as reported, , moreover, Mg atoms are active and reductive, it is reasonable to utilize Mg atoms to reduce oxides into metallic atoms in a diffusion alloying process. , …”
Section: Introductionmentioning
confidence: 99%
“…24,25 Because Mg atoms could pass through the MgO film and be oxidized there as reported, 21,22 moreover, Mg atoms are active and reductive, it is reasonable to utilize Mg atoms to reduce oxides into metallic atoms in a diffusion alloying process. 26,27 However, how do the as-reduced metallic atoms cross the MgO film and arrive at the magnesium alloy matrix is still an issue to be clarified. In this research, a diffusion source that contains ZnO powder and NH 4 Cl powder was utilized in the powder thermal diffusion alloying process on the magnesium alloy specimens.…”
Section: Introductionmentioning
confidence: 99%